Analisis Faktor-Faktor yang Mempengaruhi Pengembangan Profesi Guru di Era Digital - Ulfa Fatimah; Asianna Manik; Paiman Eliazer Nadeak; Sri Yunita (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
Teacher professional development in the digital era is a complex challenge influenced by various interrelated factors. This study aims to analyze the main factors that influence the development of teachers' professional competencies in a digital context. Digital technologies, including internet access, hardware, software, and online learning platforms, are key elements in improving teachers' competencies. Training and professional development that emphasizes the use of technology in learning is essential to prepare teachers for these changes. Support from school leadership and government through policies, programs and incentives also play an important role in supporting teachers to develop digital skills. Adaptive and flexible curricula enable the integration of technology in teaching, while collaboration between schools, teachers, parents and communities creates a supportive environment for teachers' professional development. Teachers' intrinsic motivation to continuously learn and adapt to changes in technology and pedagogy is influential. With good management of these factors, the quality of teaching and student learning outcomes can improve, as well as advance the teaching profession in the digital era.